Contributions to a history of theater in prisons in Brazil (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Aspects of theater in prisons in Brazil, lays out a timeline that includes historical antecedents of this theater modality, and lists theater experiences in Brazilian prisons from 1937 to 2019. In view of the necessary systematization of studies on the theme, this article certainly does not record all theater experiences in our prisons, but this research complements the historical panorama of theater in prisons elaborated by Concilio (2008) in his master's dissertation. The article covers debates in the field as well as aspects of the relationship between art and prison in the national context in a historicized perspective.
Keywords: Theater and Prison; Theater and Incarceration; History of theater